0363 Perceptions of the Need for Perioperative OSA Education: An Interdisciplinary and Multi-Institutional Survey. (25th May 2022) - Lyons, M Melanie; Gali, Bhargavi; Auckley, Dennis; Mokhlesi, Babak; Myers, John; Charchaflieh, Jean; Yilmaz, Meltem; Williams, Lisa; Khan, Meena; Card, Elizabeth; Gelfand, Brain; Pilla, Michael; et al.
Abstract: Introduction: Advanced Practice Providers (APPs; Advanced practice registered nurses, physician assistants) and physicians-in-training (residents, fellows) receive inadequate education on obstructive sleep apnea (OSA)/perioperative OSA risks. However, they are front-line providers assessing these patients. Failure to mitigate this risk has led to significant postoperative morbidity/mortality. We assessed these providers' perceptions to OSA/perioperative OSA training. Methods: Surveys were sent to three provider roles, APPs, residents, and fellows, in four categories of practice at nine academic institutions between May 9-June 30, 2021. Chi-square and Fisher's exact tests assessed association between survey responses and participant characteristics. False discovery rate adjustment accounted for multiple comparisons, threshold of q<0.05 for statistical significance. Cochran-Mantel-Haenzsel tests evaluated associations stratified by institution. Results: 2236 of 6724 (33.3%) participants responded: 48.4% APPs, 11% Fellows and 40.6% Residents. Primary category of practice included: 20.3% Anesthesiology, 8.9% Family Medicine, 34.1%, Internal Medicine (IM)/IM subspecialties, 6.7% Obstetrics/Gynecology/Gynecologic Oncology, 25.9% Surgery/Surgery subspecialties, 4.1% Other.While 93.2% of respondents believed OSA is a risk factor for perioperative complications, fewer respondents reported that they felt adequately trained to assess for OSA (50.9%) in general, with significant differences noted by provider role (range 42-70%, q=0.001) and across the categories of practice (range 12-82%, q=0.001). Even fewer felt adequately trained to assess for OSA in perioperative patients (38.2%) with significant differences noted by provider role (range 31-52%, q=0.001) and across the categories of practice (range 15-84%, q=0.001).Across all categories of practice, respondents indicated that they would like additional educational training about OSA (76.7%). This varied by clinical role (range 64-82%, q=0.003), but not categories of practice (range 73-84%, q=0.13). Furthermore, respondents indicated they also desired additional education about OSA in the perioperative patient (75.5%). This extended across all clinical roles (range 68-77%, q=0.09) and categories of practice (range 72-80%, q=0.09). Conclusion: We found significant differences in APP and physician-in-training perceptions of the adequacy of their current training and desire for further OSA/perioperative OSA education. Our study identifies a critical gap and opportunity to improve provider understanding and patient care. Support (If Any): American Academy of Sleep Medicine Foundation (AASMF) award.